C by example - Kalicharan, Noel. (Cambridge ; New York : Cambridge University Press, 1994)
C is one of the most popular programming languages today. It is flexible, efficient and highly portable, and is used for writing many different kinds of programs, from compilers and assemblers to spreadsheets and games. This book is based on ANSI C - the recently adopted standard for the C language. It assumes familiarity with basic programming concepts such as variables, constants, iteration and looping, but covers all aspects of C. In general it is as much about learning programming skills as it is about mastering the art of coding programs in C. To this end the text contains a wealth of examples and exercises that foster and test the understanding of the concepts developed in each chapter.
1. Getting Started With C -- 2. More Control Structures and Arrays -- 3. Functions - the Basics -- 4. Character Handling -- 5. Functions and Pointers -- 6. Data Types, Operators and Storage Classes -- 7. Basic Structures and Linked Lists -- 8. Binary Trees and Other Structures -- 9. Standard Input/Output -- 10. File Input/Output -- 11. Miscellaneous Topics -- App. A List of C keywords -- App. B Differences between ANSI C and traditional C -- App. C ASCII character set.
Includes index.
Keywords: C (Computer program language)